Prevalence of exposure to someone else’s firearm violence, threats, and risky behavior among a national sample of young people in the United States - Mitchell, Kimberly J.; Banyard, Victoria; Taylor, Bruce G.; Mumford, Elizabeth A.; Liu, Weiwei; Turner, Heather A. (Frontiers in Public Health, 2025)
This article provides prevalence rates for a wide range of types of exposure to someone else’s firearm violence, threats, and risky behavior among youth and young adults across several different demographic and structural characteristics. Data are from the Growing Up with Guns study of 5,311 participants recruited through the AmeriSpeak Panel. Data were collected from September 2023 to January 2024. Eligibility included U.S. residents who were ages 10–34 years old and proficient in either English or Spanish. A majority of participants (69.5%) reported exposure to someone else’s firearm violence, threats, or risky firearm behavior—either interpersonal or self-directed—in their lifetime. Rates of exposure were high across age categories, ranging from 48.0% of 10–17 year olds to 80.3% of 25–34 year olds. Odds of exposure also varied by race, sexual minority identity as well as deficits in social determinants of health (SDOH). Such wide-spread exposure introduces opportunities to prevent shootings before they occur and can inform the development of bystander interventions targeting those who are witnesses or otherwise know about another person’s firearm violence, threats or risky behaviors.